Changes in the electrical and viscoelastic parameters of erythrocytes in patients with manifestations of metabolic syndrome, COVID-19 convalescents, when exposed to citicoline in an in vitro experiment - Margarita V. Kruchinina; Andrei A. Gromov; Elina V. Kruchinina; Yulia A. Shishakina (ZAO "Consilium Medicum", 2023)
Aim. To study changes in the electrical and viscoelastic parameters of erythrocytes using the method of dielectrophoresis in patients with manifestations of the metabolic syndrome who underwent COVID-19, when exposed to the drug citicoline in an in vitro experiment to reduce the severity of microcirculatory disorders. Materials and methods. 31 men were examined with manifestations of metabolic syndrome (50.6±9.9 years), COVID-19 convalescences, within 8 to 12 months after the disease, the diagnosis was confirmed by PCR, ELISA. The electrical and viscoelastic parameters of erythrocytes were studied by dielectrophoresis twice: the initial levels of indicators were determined and after 30 minutes of exposure with after 30 minutes of exposure to a solution of the drug Ronocyte (oral solution with the active substance citicoline sodium - 104.50 mg., which is equivalent to 100.00 mg citicoline at a concentration of 0.01 µl per 0.3 µl of red blood cell suspension in 0.3M sucrose solution (pH 7.36). Results. Exposure of erythrocyte suspension of patients with Ronocyte solution led to change in the levels of electrical, viscoelastic parameters: an increase in the average cell diameter (p=0.0003), the proportion of discocytes (p=0.0004), the amplitude of cell deformation at high frequencies of the electric field (p=0.000002), cell capacity (p=0.000007), the velocity of erythrocytes to the electrodes (p=0.003), dipole moment (p=0.002), polarizability at 106 and 0.5×106 Hz (p=0.000019 and p=0.0015, respectively), relative polarizability (p0.05) and, conversely, to reduce summarized rigidity (p=0.000003), viscosity (p=0.000002), electrical conductivity (p0.000001), aggregation indices (p=0.00003), destruction at frequencies of 106 Hz (p=0.003), 0.5x106 Hz (p=0.00002), 0.1×106 Hz (p0.00001), polarizability at low frequencies of the electric field (p=0.02). Under the influence of the drug, the equilibrium frequency of erythrocytes shifted to the low-frequency range compared to the initial values (p0.0000001). The revealed changes indicate an increase in the surface charge of erythrocytes, their ability to deform, and cell resistance under the action of citicoline. Conclusion. For the first time, the effect of the drug with the active substance citicoline, improving the rheological properties of erythrocytes, was discovered. Preparations with the active substance - citicoline should be considered promising for conducting a full-fledged clinical study to study the reduction of circulatory disorders at the microcirculatory level in patients with manifestations of metabolic syndrome who have undergone COVID-19 coronavirus infection.